(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Financial Performance Analysis of Rural Bank in Gianyar Regency Before and During the New Normal Era. The COVID-19 pandemic has become a new chapter in human global civilization called the new normal era. The impact felt in this new normal era is very large, one of which has an impact on the financial performance of Rural Banks (BPR). This study aims to analyze the financial performance of BPR in Gianyar Regency before and during the new normal era using the CAMEL method which includes indicators of Minimum Capital Adequacy Ratio (KPMM), Earning Assets Quality (KAP), Allowance for Earning Assets Losses (PPAP), Management, Return on Assets (ROA), Operating Expenses to Operating Income (BOPO), Cash Ratio (CR), and Loan to Deposit Ratio. The results of this study indicate that there are significant differences in the values of CAR, ROA, BOPO, and CR BPR in Gianyar Regency before and during the new normal era. Meanwhile, there is no significant difference between the values of KAP, PPAP, Management, and LDR BPR in Gianyar Regency before and during the new normal era.